2017
DOI: 10.1002/apj.2077
|View full text |Cite
|
Sign up to set email alerts
|

Parametric investigation of polymethacrylate monolith synthesis and stability via thermogravimetric characterisation

Abstract: Polymethacrylate monoliths are synthetic adsorbents with macroporous and mesoporous interconnected channels that can be engineered to target the hydrodynamic features of a wide range of molecular species. However, rigorous study into the effect of synthesis conditions on their thermal stability is limited. This work attempts to characterise the influence of key synthesis process variables on the stability of polymethacrylate monoliths using thermogravimetric analysis at a heating rate of 10°C/min. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This is due to their intriguing properties of high surface area, chemical stability, and high pore volumes. Higher permeability and reduced flow resistance as a result of the interconnected pores enable high-speed separation providing high throughput, resolution, and separation in short run times [5,6]. It is important that the porosity of the monolith is well structured to enable mass transport and diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their intriguing properties of high surface area, chemical stability, and high pore volumes. Higher permeability and reduced flow resistance as a result of the interconnected pores enable high-speed separation providing high throughput, resolution, and separation in short run times [5,6]. It is important that the porosity of the monolith is well structured to enable mass transport and diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported monolith degradation at a lower temperature of around 200 °C. That monolith was made of similar monomer chemicals, but was templated using porogen as prepared by Acquah, Danquah, Moy, Anwar and Ongkudon [ 22 ]. Yusuf, et al [ 34 ] also reported initial monolith degradation at 210 °C in their study.…”
Section: Resultsmentioning
confidence: 99%
“…The first deterioration of the monolith prepared using a 60:40 template/monolith ratio occurred at 243 • C, with the second degradation beginning at 332 • C. At 700 • C, the monolith samples had been completely degraded and converted into ashes. A previous study reported monolith degradation at a lower temperature of around 200 • C. That monolith was made of similar monomer chemicals, but was templated using porogen as prepared by Acquah, Danquah, Moy, Anwar and Ongkudon [22]. Yusuf, et al [34] also reported initial monolith degradation at 210 • C in their study.…”
Section: Thermal Stability Of Microsphere-templated Porous Monolithsmentioning
confidence: 89%
See 2 more Smart Citations